Mechanical Properties of Grouted Crushed Coal with Different Grain Size Mixtures under Triaxial Compression - Yuhao Jin; Lijun Han; Qingbin Meng; Suresh Sanda; Haizhi Zang; Bing Feng (Advances in Civil Engineering)
To have a better understanding of the reinforcement effect on the crushed zone after grouting in coal mining extraction work, a self-designed grouting apparatus was used to study the effects of the grain size mixtures (distribution) and the stress state on the mechanical behaviours of grouted crushed coal specimens. From the various grouting tests, triaxial compression tests and scanning electron microscopy (SEM) observations of grouted specimens with different grain size mixtures, it was found that, for the same grain size mixture, the peak (σp) and residual (σr) strengths of the grouted specimens increased with an increase in confining pressure. It was found that the average slope values of the σp-σ3 curves for the grouted specimens with different grain size mixtures were all larger than those of the σr-σ3 curves. It was observed that the peak strain (εp) of the grouted specimens with different grain size mixtures increased overall with increasing confining pressure. For constant confining pressure, the peak and residual strengths both gradually increased approximately linearly as the grain size mixtures varied from small to large, but at higher confining pressures, the influence of the grain size mixture on the peak (or residual) strength increased. These mechanical behaviours of the grouted crushed coal specimens were strongly dependent on the variation in the grain size mixtures and in the confining pressure, which can be explained by the crack evolution process within the grouted specimen under triaxial compression, to a certain extent. Ultimate failure of the grouted specimen occurred just after propagation and coalescence of the cracks through the entire grouted specimen. Moreover, there were three major microscopic diffusion modes for the grouts flowing in most of the crushed coal specimens. Based on these test results, it was found that the reinforcement effect of the grouted specimen related to the splitting grouting mode (occurring in most of the large specimens) seems to be better than that of the penetrating (filling) grouting mode (in most of the small specimens).